An ESP textbook evaluation: the case of English for Islamic Insight - Faizatul Istiqomah; Binti Maunah (JETLe (Journal of English Language Teaching and Learning), 2020)
Abstract. The crucial presence of instructional materials at English classes, especially English for Specific Purposes, has commonly been approved. ESP materials provide exposure to the genres needed by the students, including those at Islamic Education Department. It is, therefore, inevitable that the textbook meets some criteria for the success of the program. In this paper, the writers evaluated an ESP textbook institutionally prepared for students of Tarbiyah and Teacher Training Faculty at IAIN Tulungagung. The analysis in this qualitative descriptive research was based on Cunningsworth’s and Miekley’s checklists for textbook evaluation. The book was evaluated on the category of aims and approaches, design and organization, content, skills, topic, methodology, vocabulary and grammar, exercises and activities, attractiveness of the text and physical make up, context, and practical considerations. The results showed that almost all categories are marked as adequate. It is indicated that the textbook mainly focused on vocabulary enrichment. Some recommendations for textbook improvement and revision are given at the final part of this study, particularly those related to the challenge on the advanced of technology.Keywords. ESP; Textbook Evaluation; English for Islamic Insight